Ta’līm Al-Mufrādāt Al Qāim A’lā Al Masyrū’ Fī Dhoui Al Manhaj Al Istiqlālī Fī Al Madrasah Al Tsānawīyah Al Hukūmiyyah Batu - Nopriansyah, Beri; Wargadinata, Wildana; Fikri, Shofil (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Arabic language learning in MTs has a strategic role in equipping students with communication skills, both verbally and in writing. One important aspect of mastering Arabic is vocabulary. However, vocabulary learning in madrasas often faces challenges, such as monotonous methods, minimal active student involvement, and a less contextual approach. This circumstance has an impact on low motivation and slow improvement in vocabulary mastery. This study aims to explore how project-based vocabulary learning is implemented using the independent curriculum approachach at MTsN Batu. We collected data through observation, interviews, and documentation studies, using a qualitative approach and a case study method.he results of the study indicate that the purpose of this learning is to improve students' understanding and skills through contextual, practical, and competency-based learning experiences. The steps include asking basic questions, project planning, determining project schedules, project assessments, and evaluating experiences. However, the evaluation stage of experiences has not been optimal due to time constraints. The advantages of this method include training independence and responsibility, increasing motivation, and training collaboration. Meanwhile, the disadvantages are that it takes longer, the teacher's burden is heavier, and there are variations in student abilities. Overall, this method has a positive impact on student engagement and understanding of Arabic vocabulary. For optimization, a more targeted mentoring strategy, good time management, and sufficient support for teachers are needed in implementing it.